Determination of Intrinsic Permeability for Packed Waste of Indonesian Solid Waste - Rahardyan, Benno; Dwirestiani, Retno; Padmi, Tri (Journal of Engineering and Technological Sciences, 2010)
Gas permeability and intrinsic permeability are the major parameters to promote aeration for packed waste. The objectives of this research are to identify physical parameters of gas transfer from a various type of packed wastes and examine ventilation design theory for landfill to enhance waste stabilization. Method to determine value of gas permeability and intrinsic permeability for packed waste is by flushing the packed column containing various type and physical characteristics of wastes with an air pump. Permeability was calculated by measuring pressure gradient on sampling points of the column using inclined manometer at distance 10 cm, 23 cm, 46 cm, 69 cm, 92 cm and 115 cm from origin. Gas permeability is specifically relied on physical parameters of wastes as follows, density, moisture content, particle size and gas velocity on the surface of compacted waste layer. Compost has finer pore structure and smaller pore size than leaves as well as mixed organic (65%) and inorganic wastes (35%). The experiment found the intrinsic permeability of leaves waste are in the order of 10-11 to 10-8 m2, 10-11 to 10-9 m2 for compost and 10-9 m2 for mixed organic (65%) and inorganic wastes (35%).